Optimalisasi Fungsi Manajemen Kepala Ruangan terhadap Perilaku Etik Perawat dalam Pelayanan Keperawatan - Novi Sandra Hasibuan; Hanny Handiyani; Nurhayati Nurhayati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the description of the perception of ethical behavior of the head of the room, and the process of making innovations to the problems that occur, ethical behavior in nursing services. The method used in this research is a case study. The results showed that, the majority of the head of the room perceived, had good concern for ethical issues as many as 10 (52.7%) respondents, with, the majority of the head of the room perceived, had moderate difficulty in applying ethics as many as 11 (57.9%) respondents. The majority of the head of the room perceived that they considered ethical issues very well as many as 11 (57.9%) respondents. The innovations that are arranged in solving ethical behavior problems are SOPs and forms of alleged ethical cases. In conclusion, the implementation of the ward head's ethical behavior on ethical issues can be categorized as being carried out well at Hospital X Jakarta. Keywords: Planning Function, Head of Room, Nursing Ethical Behavior